Separator for lithium ion battery
By using polypropylene resin and modified lignin, lithium-ion battery separators with porous structure and good compatibility were prepared, which solved the safety hazards and low compatibility of existing separators when approaching the melting point, and achieved Higher stability, capacity and flame retardant properties.
Patent Information
- Application Number
- CN202411645724.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The material will melt and shrink when the existing lithium-ion battery separator approaches the melting point, resulting in safety risks. The material has low compatibility and poor flame retardant performance, which can easily ignite and expand the fire.
Polypropylene resin is used as the matrix, and pore-forming agent, modified lignin, initiator and antioxidant are added. Through double-screw extrusion, cooling and shaping, stretching and high-temperature heat setting, a good phase with a porous structure is prepared. Capacitive and flame retardant diaphragm.
It improves the corrosion resistance, mechanical properties of the diaphragm, the stability, capacity and charge and discharge performance of the battery, and at the same time enhances the antioxidant and flame retardant properties of the diaphragm, reducing the safety hazards of the battery.
Smart Images

Figure BDA0005139646430000031 
Figure BDA0005139646430000041 
Figure BDA0005139646430000042
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular, relates to a diaphragm for lithium ion batteries. Background Art
[0002] With the rapid development of mobile phones and new energy vehicles, the development of high-energy power equipment, especially lithium battery industry, has been promoted worldwide. Lithium-ion batteries are regarded as a common energy storage device with broad market prospects and rapid development due to their high working voltage and specific energy, fast charge and discharge, and high safety performance.
[0003] Lithium batteries are mainly composed of four functional components: positive electrode, electrolyte, diaphragm, and negative electrode. Among them, the diaphragm is an important component of the internal components of lithium-ion batteries. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle, and safety performance. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. For lithium battery series, since the electrolyte is an organic solvent system, a diaphragm material resistant to organic solvents is required, and a high-strength thin-film polyolefin porous membrane is generally used. However, as the demand for lithium batteries continues to increase, in order to obtain high capacity and provide high power, a battery usually needs to use dozens or even hundreds of batteries in series. Therefore, lithium batteries have potential explosion hazards, and the safety of the diaphragm is very important. However, whether polyethylene, polypropylene or other polyolefin materials, when approaching the melting point, the material will shrink and deform due to melting, which brings potential hidden dangers to the safety of lithium batteries. Moreover, polyolefin materials lack polar functional groups and have low compatibility with highly polar electrolytes, resulting in poor wettability and high impedance during ion migration. Finally, polyolefin materials have a low oxygen index and poor flame retardancy. Once a fire occurs, this type of diaphragm is very easy to ignite and there is a risk of dripping and expanding the fire. Therefore, it is urgent to invent a lithium-ion battery diaphragm that can solve the above problems to meet the higher demands in the field of lithium-ion battery technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a separator for a lithium ion battery.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A separator for a lithium ion battery is prepared by the following steps:
[0007] After the polypropylene resin is dried in an oven, it is first mixed with a pore-forming agent at a high speed, and then added into a twin-screw extruder with modified lignin, an initiator and an antioxidant, melt-blended and extruded, cooled and shaped, and then longitudinally and transversely stretched to obtain a membrane. The membrane is immersed in ultrapure water for 1-2 hours, taken out, heat-shaped at high temperature, and rolled up to obtain a separator for lithium-ion batteries.
[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 60-80 parts of polypropylene resin, 18-30 parts of pore formers, 5-15 parts of modified lignin, 0.1-0.2 parts of initiators, and 3-9 parts of antioxidants.
[0009] Furthermore, the pore-forming agent is one of carboxymethyl cellulose, polyvinyl pyrrolidone and methyl cellulose.
[0010] Furthermore, the initiator is one of benzoyl peroxide and lauroyl peroxide.
[0011] Furthermore, the antioxidant is prepared by compounding a hindered phenol antioxidant and a thioester antioxidant in a mass ratio of 2:1.
[0012] With polypropylene as the matrix, the diaphragm has excellent corrosion resistance and mechanical properties; the added pore-forming agent is an organic pore-forming agent, which will decompose and produce gas, so that the diaphragm forms a porous structure. The porous structure has a higher specific surface area and more active material contact surface, thereby improving the capacity and charge and discharge performance of the battery, and the porous structure is conducive to the diffusion and reaction of the electrolyte, thereby improving the stability of the battery; finally, the added antioxidants are hindered phenol antioxidants and thioester auxiliary antioxidants, the two can play a synergistic role and greatly enhance the antioxidant properties of the diaphragm.
[0013] Furthermore, the modified lignin is prepared by the following steps:
[0014] S1. Add 2-hydrazinoethanol, diethyl carbonate and sodium methoxide to a three-necked flask, react at 80°C for 2h, cool to precipitate a solid, filter with suction to obtain a dry solid; evaporate the filtrate to remove the solvent, separate by column chromatography (the volume ratio of methanol to dichloromethane is 1:35) to obtain a white solid, mix the dry solid with the white solid, add ether, stir for 10min, filter to obtain intermediate 1; the ratio of 2-hydrazinoethanol, diethyl carbonate, sodium methoxide and ether is 7.6g:11.7g:0.1g:50mL;
[0015] 2-Hydrazinoethanol reacts with diethyl carbonate to generate intermediate 1; the specific reaction process is as follows:
[0016]
[0017] S2. In a three-necked flask equipped with a stirring reflux device at room temperature, add intermediate 1, diethylene glycol dimethyl ether and N,N-diisopropylethylamine (catalyst) and mix well, place in an ice bath at 2°C, add ethylene trichlorosilane dropwise, and control the temperature not to exceed 15°C during the addition. After the addition is completed, reflux at 90°C for 10 hours. After the reaction is completed, filter, remove part of the solvent by rotary evaporation, and purify by column chromatography (the eluent is a mixed solvent of chloroform / ethyl acetate in a volume ratio of 2:3), remove the eluent by rotary evaporation, and vacuum dry to obtain intermediate 2; the ratio of the amount of intermediate 1, diethylene glycol dimethyl ether, N,N-diisopropylethylamine, and ethylene trichlorosilane is 20.4g:100mL:30mL:16.4g;
[0018] Under the catalysis of N,N-diisopropylethylamine, intermediate 1 reacts with ethylene trichlorosilane, and intermediate 2 is obtained by controlling the molar ratio of the two to be close to 2:1 and ethylene trichlorosilane to be slightly excessive. The reaction process is as follows:
[0019]
[0020] S3. In a three-necked flask equipped with a stirring device at room temperature, the intermediate 2, decanediamine, N,N-dimethylformamide (DMF) and N,N-diisopropylethylamine were mixed evenly, and the temperature was raised to 85°C for 8 hours of heat preservation. After the reaction was completed, it was filtered, distilled under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 4:1), the eluent was removed by rotary evaporation, and vacuum dried to obtain intermediate 3; the ratio of the amount of intermediate 2, decanediamine, N,N-dimethylformamide, and N,N-diisopropylethylamine was 29.2g:18.7g:150mL:15mL;
[0021] Under the catalysis of N,N-diisopropylethylamine, intermediate 2 reacts with decanediamine, and intermediate 3 is obtained by controlling the molar ratio of the two to be close to 1:1 and the amount of decanediamine is slightly excessive. The specific reaction process is as follows:
[0022]
[0023] S4. In a three-necked flask equipped with a stirring device, the intermediate 3, glutaryl chloride and N,N-dimethylformamide were mixed and stirred continuously for 5 minutes, and then dicyclohexylcarbodiimide (DCC) was added, and the mixture was kept in a water bath at 55°C for 8 hours. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 4:1), and the eluent was removed by rotary evaporation to obtain a modifier. The ratio of the amount of the intermediate 3, glutaryl chloride, N,N-dimethylformamide and DCC was 42.8 g:18.4 g:150 mL:20.6 g.
[0024] Under the catalysis of DCC, the intermediate 3 and glutaryl chloride undergo an amidation reaction, and a modifier is obtained by controlling the molar ratio of the two to be close to 1:1 and a slight excess of glutaryl chloride; the structure of the modifier is shown below:
[0025]
[0026] S5. Add dried, ground lignin and N,N-dimethylformamide to a three-necked flask, stir to fully dissolve the lignin, add a modifier and pyridine (catalyst), place the three-necked flask on a magnetic stirring heating device for heating, control the reaction temperature to 70°C, stir the reaction for 3 hours, and after the reaction is completed, filter, wash, and dry to obtain modified lignin; the ratio of lignin, N,N-dimethylformamide, modifier, and pyridine is 1g:100mL:12.7g:10mL;
[0027] The hydroxyl groups on the surface of lignin react with the acyl chloride groups in the modifier molecules to undergo an esterification reaction, connecting the modifier to the lignin to obtain modified lignin;
[0028] Lignin contains abundant polar groups and has good wettability. Moreover, lignin has a benzene ring structure, which also makes lignin have a better rigid chain structure than other natural macromolecules, making it have higher heat resistance and certain flame retardant properties. In addition, by esterification modification of lignin, the interfacial compatibility between lignin and polypropylene matrix can be improved, and the modified lignin can be evenly dispersed in the matrix, so that the performance of the modified lignin can be fully exerted, and the heat resistance and flame retardant properties of the matrix can be greatly enhanced to a certain extent. The wettability of the matrix can also be enhanced, the compatibility between the separator and the electrolyte can be improved, the impedance of ion migration can be reduced, the lithium ion transmission speed can be enhanced, and the battery life can be improved. Cyclic performance; in addition, the modified lignin molecule also contains oxazolidinone, Si-N flame retardant components, long carbon chains and carbon-carbon double bonds, among which the Si-N flame retardant component has the synergistic flame retardant effect of silicon-based and nitrogen-based flame retardants, and Si-N is a covalent bond with stable physical and chemical properties. When burned, it generates a denser Si-C or Si-Si layer with outstanding flame retardant effect; the introduced oxazolidinone has strong heat resistance and can increase the thermal decomposition temperature of the matrix; the introduced long carbon chain is a methylene chain segment, which is a flexible chain segment and can enhance the mechanical properties of the matrix to a certain extent; finally, the introduction of carbon-carbon double bonds can produce cross-linking with the matrix under the action of a catalyst to improve the stability of lignin;
[0029] It should be noted that grafting a modifier onto lignin can improve the resistance of the small molecules of the modifier to migration and exudation, so that the modified lignin can perform its performance stably for a long time.
[0030] Beneficial effects of the present invention:
[0031] 1. The diaphragm prepared by the present invention is based on polypropylene, which gives the diaphragm excellent corrosion resistance and mechanical properties;
[0032] 2. Adding organic pore-forming agents makes the diaphragm form a porous structure, thereby improving the stability, capacity and charge and discharge performance of the battery;
[0033] 3. The added antioxidant has a synergistic effect, greatly improving the antioxidant performance of the diaphragm;
[0034] 4. By modifying lignin, it has better compatibility with the polypropylene matrix than ordinary lignin, and can also enhance the wettability, flame retardancy, heat resistance and mechanical properties of the diaphragm. The performance is long-lasting and stable and not easy to fall off;
[0035] Therefore, the diaphragm prepared by the present invention has a porous structure, good wettability and anti-oxidation properties, and also has stable and efficient flame retardancy, heat resistance and mechanical properties, and has important application value in the field of lithium ion battery technology. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Embodiment 1
[0038] Preparation of modified lignin:
[0039] S1. Add 7.6 g of 2-hydrazinoethanol, 11.7 g of diethyl carbonate and 0.1 g of sodium methoxide into a three-necked flask, react at 80° C. for 2 h, cool to precipitate a solid, filter with suction to obtain a dry solid; evaporate the filtrate to remove the solvent, separate by column chromatography (the volume ratio of methanol to dichloromethane is 1:35) to obtain a white solid, mix the dry solid with the white solid, add 50 mL of ether, stir for 10 min, and filter to obtain intermediate 1;
[0040] S2. In a three-necked flask equipped with a stirring reflux device at room temperature, 20.4 g of intermediate 1, 100 mL of diethylene glycol dimethyl ether and 30 mL of N,N-diisopropylethylamine were added, mixed evenly, placed in an ice bath at 2°C, 16.4 g of ethylenetrichlorosilane was added dropwise, and the temperature was controlled not to exceed 15°C during the addition. After the addition was completed, reflux reaction was carried out at 90°C for 10 hours. After the reaction was completed, the mixture was filtered, and some solvents were removed by rotary evaporation. The mixture was purified by column chromatography (the eluent was a mixed solvent of chloroform / ethyl acetate in a volume ratio of 2:3), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 2.
[0041] S3. At room temperature, in a three-necked flask equipped with a stirring device, 29.2 g of intermediate 2, 18.7 g of decanediamine, 150 mL of N,N-dimethylformamide and 15 mL of N,N-diisopropylethylamine were mixed evenly, and the temperature was raised to 85°C for 8 h of heat preservation. After the reaction was completed, the mixture was filtered, evaporated under reduced pressure, and purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 4:1), the eluent was removed by rotary evaporation, and vacuum dried to obtain intermediate 3;
[0042] S4. In a three-necked flask equipped with a stirring device, 42.8 g of intermediate 3, 18.4 g of glutaryl chloride and 150 mL of N,N-dimethylformamide were mixed and stirred continuously for 5 min, and then 20.6 g of dicyclohexylcarbodiimide was added. The mixture was kept in a water bath at 55°C for 8 h. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 4:1), and the eluent was removed by rotary evaporation to obtain a modifier.
[0043] S5. Add 1 g of dried, ground lignin and 100 mL of N,N-dimethylformamide into a three-necked flask, stir to fully dissolve the lignin, add 12.7 g of modifier and 10 mL of pyridine, place the three-necked flask on a magnetic stirring heating device for heating, control the reaction temperature to 70°C, stir the reaction for 3 hours, and after the reaction is completed, filter, wash, and dry to obtain modified lignin.
[0044] Embodiment 2
[0045] Preparation of modified lignin:
[0046] S1. Add 15.2 g of 2-hydrazinoethanol, 23.4 g of diethyl carbonate and 0.2 g of sodium methoxide into a three-necked flask, react at 80° C. for 2 h, cool to precipitate a solid, filter with suction to obtain a dry solid; evaporate the filtrate to remove the solvent, separate by column chromatography (the volume ratio of methanol to dichloromethane is 1:35) to obtain a white solid, mix the dry solid with the white solid, add 100 mL of ether, stir for 10 min, and filter to obtain intermediate 1;
[0047] S2. In a three-necked flask equipped with a stirring reflux device at room temperature, 40.8 g of intermediate 1, 200 mL of diethylene glycol dimethyl ether and 60 mL of N,N-diisopropylethylamine were added, mixed evenly, placed in an ice bath at 2°C, 32.8 g of ethylenetrichlorosilane was added dropwise, and the temperature was controlled not to exceed 15°C during the addition. After the addition was completed, reflux reaction was carried out at 90°C for 10 hours. After the reaction was completed, the mixture was filtered, and some solvents were removed by rotary evaporation. The mixture was purified by column chromatography (the eluent was a mixed solvent of chloroform / ethyl acetate in a volume ratio of 2:3), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 2.
[0048] S3. At room temperature, in a three-necked flask equipped with a stirring device, 58.4 g of intermediate 2, 37.4 g of decanediamine, 300 mL of N,N-dimethylformamide and 30 mL of N,N-diisopropylethylamine were mixed evenly, and the temperature was raised to 85°C for 8 hours of insulation. After the reaction was completed, the mixture was filtered, evaporated under reduced pressure, and purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 4:1), the eluent was removed by rotary evaporation, and vacuum dried to obtain intermediate 3;
[0049] S4. In a three-necked flask equipped with a stirring device, 85.6 g of intermediate 3, 36.8 g of glutaryl chloride and 300 mL of N,N-dimethylformamide were mixed and stirred continuously for 5 min, and then 41.2 g of dicyclohexylcarbodiimide was added. The mixture was kept in a water bath at 55°C for 8 h. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate in a volume ratio of 4:1), and the eluent was removed by rotary evaporation to obtain a modifier.
[0050] S5. Add 2 g of dried, ground lignin and 200 mL of N,N-dimethylformamide into a three-necked flask, stir to fully dissolve the lignin, add 25.4 g of modifier and 20 mL of pyridine, place the three-necked flask on a magnetic stirring heating device for heating, control the reaction temperature to 70°C, stir the reaction for 3 hours, and after the reaction is completed, filter, wash, and dry to obtain modified lignin.
[0051] Embodiment 3
[0052] After drying 60g of polypropylene resin in an oven, it was first mixed with 18g of carboxymethyl cellulose at a high speed, and then added into a twin-screw extruder with 5g of the modified lignin prepared in Example 1, 0.1g of benzoyl peroxide and 3g of antioxidant (prepared by compounding 2g of antioxidant 1010 and 1g of lauryl thiodipropionate), melt-blended and extruded, cooled and shaped, and then longitudinally stretched and transversely stretched to obtain a membrane. After immersing the membrane in ultrapure water for 1h, it was taken out, subjected to high-temperature heat setting, and rolled up to obtain a separator for a lithium ion battery.
[0053] Embodiment 4
[0054] After drying 70g of polypropylene resin in an oven, it is first mixed with 24g of polyvinyl pyrrolidone at a high speed, and then added into a twin-screw extruder with 10g of the modified lignin prepared in Example 2, 0.2g of lauroyl peroxide and 6g of antioxidant (prepared by compounding 4g of antioxidant 1010 and 2g of lauryl thiodipropionate), melt-blended and extruded, cooled and shaped, and then longitudinally stretched and transversely stretched to obtain a membrane. After immersing the membrane in ultrapure water for 2h, it is taken out, subjected to high-temperature heat setting, and rolled up to obtain a separator for a lithium ion battery.
[0055] Embodiment 5
[0056] After drying 80g of polypropylene resin in an oven, it is first mixed with 30g of methyl cellulose at a high speed, and then added into a twin-screw extruder with 15g of the modified lignin prepared in Example 2, 0.2g of lauryl peroxide and 9g of antioxidant (prepared by compounding 6g of antioxidant 1010 and 3g of lauryl thiodipropionate), melt-blended and extruded, cooled and shaped, and then longitudinally stretched and transversely stretched to obtain a membrane. After immersing the membrane in ultrapure water for 2h, it is taken out, subjected to high-temperature heat setting, and rolled up to obtain a separator for a lithium ion battery.
[0057] Comparative Example 1
[0058] The modified lignin in Example 5 was replaced by ordinary lignin of the same mass, and the remaining steps were the same as those in Example 5 to prepare a diaphragm.
[0059] Comparative Example 2
[0060] 130 g of commercially available heat-resistant flame-retardant polypropylene masterbatch was added to a twin-screw extruder, melt-extruded, cooled and shaped, and then longitudinally and transversely stretched to obtain a membrane. The membrane was immersed in ultrapure water for 2 hours, taken out, heat-shaped at high temperature, and rolled up to obtain a diaphragm.
[0061] The following performance tests were performed on Examples 3, 4, and 5 and Comparative Examples 1 and 2:
[0062] Use a thickness gauge to test the thickness of the sample at 25°C;
[0063] The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to measure the limiting oxygen index of the sample before and after being placed at room temperature for 180 days;
[0064] The national standard GB / T 36363-2018 "Polyolefin separators for lithium-ion batteries" was used to measure the thermal shrinkage and puncture strength of the samples;
[0065] The mass of the dry battery diaphragm is recorded as M0, and then the diaphragm is completely immersed in the electrolyte, the residual electrolyte on the surface is carefully wiped off with filter paper, and it is weighed again. The weight at this time is recorded as M1. The calculation formula for the liquid absorption rate is as follows: (M1-M0) / M0×100%.
[0066] The measured results are shown in Table 1:
[0067] Table 1
[0068]
[0069]
[0070] The samples of Examples 3, 4, 5, and Comparative Examples 1 and 2 were used as separators for lithium batteries, and the relevant electrochemical performance tests were performed. The results are shown in Table 2:
[0071] Table 2
[0072]
[0073] It can be seen from the above two tables that the wettability, flame retardancy, heat resistance and mechanical properties of the diaphragm prepared in the embodiment of the present invention are higher than those of the control example, and the performance is long-lasting and stable. The battery made using the diaphragm as a raw material has a large capacity and good cycle performance. In summary, the diaphragm prepared in the present invention has important application value in the field of lithium-ion battery technology.
[0074] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0075] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A separator for a lithium-ion battery, characterized in that: Prepared by the following steps: After the polypropylene resin is dried, it is first mixed with a pore-forming agent at high speed, and then added into a twin-screw extruder with modified lignin, an initiator and an antioxidant, melt-blended and extruded, cooled and shaped, and then longitudinally and transversely stretched to obtain a membrane. After the membrane is immersed in ultrapure water, it is taken out, heat-shaped at high temperature, and rolled up to obtain a diaphragm for lithium-ion batteries.
2. The separator for lithium ion battery according to claim 1, characterized in that: The modified lignin is prepared by the following steps: S1. Add 2-hydrazinoethanol, diethyl carbonate and sodium methoxide into a three-necked flask, react at 80°C for 2h, cool to precipitate a solid, filter to obtain a dry solid; evaporate the filtrate, separate by column chromatography to obtain a white solid, mix the dry solid with the white solid, add ether, stir for 10min, and filter to obtain intermediate 1; S2, after mixing intermediate 1, diethylene glycol dimethyl ether and N,N-diisopropylethylamine at room temperature, place in an ice bath at 2°C, add ethylenetrichlorosilane dropwise, reflux at 90°C for 10h, and after the reaction is complete, filter, rotary evaporate, purify by column chromatography, rotary evaporate, and dry to obtain intermediate 2; S3, after mixing intermediate 2, decanediamine, N,N-dimethylformamide and N,N-diisopropylethylamine uniformly at room temperature, heating to 85°C and keeping the temperature for reaction for 8 hours, after the reaction is completed, filtering, vacuum distillation, column chromatography purification, rotary evaporation, and vacuum drying to obtain intermediate 3; S4, the intermediate 3, glutaryl chloride and N,N-dimethylformamide were mixed and stirred continuously for 5 minutes, and then dicyclohexylcarbodiimide was added, and the mixture was kept in a water bath at 55°C for 8 hours. After the reaction was completed, the mixture was filtered, rotary evaporated, purified by column chromatography, and rotary evaporated to obtain a modifier; S5. Add dried, ground lignin and N,N-dimethylformamide into a three-necked flask, stir to fully dissolve the lignin, add the modifier and pyridine, stir and react at 70°C for 3 hours. After the reaction is completed, filter, wash and dry to obtain modified lignin.
3. The separator for lithium ion battery according to claim 2, characterized in that: In step S1, the ratio of 2-hydrazinoethanol, diethyl carbonate, sodium methoxide and diethyl ether is 7.6 g:11.7 g:0.1 g:50 mL.
4. The separator for lithium ion battery according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, diethylene glycol dimethyl ether, N,N-diisopropylethylamine, and ethylenetrichlorosilane is 20.4 g: 100 mL: 30 mL: 16.4 g.
5. The separator for lithium ion battery according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 2, decanediamine, N,N-dimethylformamide, and N,N-diisopropylethylamine is 29.2 g:18.7 g:150 mL:15 mL.
6. The separator for lithium ion battery according to claim 2, characterized in that: In step S4, the ratio of the amount of intermediate 3, glutaryl chloride, N,N-dimethylformamide, and DCC is 42.8 g:18.4 g:150 mL:20.6 g.
7. The separator for lithium ion battery according to claim 2, characterized in that: In step S5, the ratio of lignin, N,N-dimethylformamide, modifier and pyridine is 1 g:100 mL:12.7 g:10 mL.
8. The separator for lithium ion battery according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 60-80 parts of polypropylene resin, 18-30 parts of pore formers, 5-15 parts of modified lignin, 0.1-0.2 parts of initiators, and 3-9 parts of antioxidants.
9. The separator for lithium ion battery according to claim 1, characterized in that: The pore-forming agent is one of carboxymethyl cellulose, polyvinyl pyrrolidone and methyl cellulose.
10. The separator for lithium ion battery according to claim 1, characterized in that: The antioxidant is prepared by compounding a hindered phenol antioxidant and a thioester antioxidant in a mass ratio of 2:1.
Citation Information
Cited By
Lithium ion battery diaphragm as well as preparation method and application thereof
CN120581831A
